The bachelor's stand-in wife - Crosby, Susan (New York, NY : Silhouette Books, 2008)
Tycoon David Falcon needed a wife. Not someone to actually marry, but a superefficient, multitasking woman who'd keep his household humming along smoothly. Single mother Valerie Sinclair seemed the ideal candidate. Until an evening out led to an unexpected kiss. Organizing the businessman's hectic life was one thing. Wanting to share his life wasn't part of the deal. But once Valerie got a taste of being David's girlfriend -- even for just one night -- how could she go back to being his stand-in spouse?
Contains an excerpt from Overheated by Barbara Dunlop (p. [213]-217).
Keywords: Marriage -- Fiction; Love stories